Kinerja Guru di Masa Pandemi COVID-19: Emotional Intelligence Competency dan Penerapannya - Edi Kuswanto (Fakulatas Dakwah IAIN Salatiga, 2021)
This study aims to determine the effect of Emotional Intelligence Competency (EIC) on teacher performance during the COVID-19 pandemic in Demak. Exogenous variables Emotional Maturity, Emotional Competency, Emotional Sensitivity were tested for their effect on teacher performance during the COVID-19 pandemic. This study uses a quantitative research approach with purposive sampling. The data used are PAI teachers in Demak Regency as many as 101 respondents. The results of this study indicate that the value of the original sample estimate EC - PFM is positive at 0.272 with a significance of 0.001 less than 0.05, meaning that emotional competency has a positive effect on teacher performance, as well as significant emotional sensitivity at 0.000. On the other hand, EM - PFM has a significance of 0.116 which is greater than 0.05 so that it can be interpreted as having no significant effect, meaning that emotional maturity has no significant effect on teacher performance. AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh Emotional Intellegence Competency (EIC) terhadap kinerja guru pada masa pandemi COVID-19 di Demak. Variabel eksogen Emotional Maturity, Emotional Competency, Emotional Sensitivity diuji pengaruhnya terhadap kinerja guru di masa pandemi COVID-19. Penelitian ini menggunakan pendekatan penelitian kuantitatif dengan purposive sampling. Data yang digunakan adalah guru PAI yang ada di Kabupaten Demak sebanyak 101 responden. Hasil penelitian ini menunjukkan bahwa nilai original sample estimete EC - PFM adalah positif sebesar 0.272 dengan signifikansi 0.001 lebih kecil dari 0.05, artinya bahwa emotional competency berpengaruh positif terhadap teacher performance, begitu juga emotional sensitivity signifikan pada 0.000. Sebaliknya EM - PFM memiliki signifikansi 0.116 yang lebih besar dari 0.05 sehingga dapat diartikan tidak berpengaruh signifikan, artinya bahwa emotional maturity tidak berpengaruh signifikan terhadap teacher performance. Kata Kunci: kedewasaan emosional; kompetensi emosional; kepekaan emosional; kinerja guru